Determining Factors of Community Commitment in Automotive and Sneaker Communities - Moko, Wahdiyat; Barinta, Dunga Dwi; Wati, Cicik Retno (Faculty of Economics, State Islamic University of Maulana Malik Ibrahim Malang, 2021)
This study to examine the effect of brand community integration and perceived benefits on community commitment as moderated by type of community. This study uses a quantitative approach with a hypothesis testing approach. The sample of this research is the automotive and sneaker communities. The data analysis used was SEM analysis using PLS software. Variable Brand Community Integration (x1) does not have the effect of significantly at variable community commitment (Y) and the perceived benefit (X2 ) effect is significant to the variable community commitment (Y). The study explains how importance of brand community integration and perceived benefits have a contribution to building brand community commitment. Companies can pay attention to community involvement in increasing their commitment to continue using the product. Besides, Members of communities will tend to pay attention to the benefits that they get to follow the community, It is can be used by companies to improve the provision of benefits to the members, and will give benefits for the company to increase the commitment of the customers.